2021
DOI: 10.3390/molecules26195816
|View full text |Cite
|
Sign up to set email alerts
|

Cyanoarylporphyrazines with High Viscosity Sensitivity: A Step towards Dosimetry-Assisted Photodynamic Cancer Treatment

Abstract: Despite the significant relevance of photodynamic therapy (PDT) as an efficient strategy for primary and adjuvant anticancer treatment, several challenges compromise its efficiency. In order to develop an “ideal photosensitizer” and the requirements applied to photosensitizers for PDT, there is still a need for new photodynamic agents with improved photophysical and photobiological properties. In this study, we performed a detailed characterization of two tetracyanotetra(aryl)porphyrazine dyes with 4-biphenyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The assessment of viscosity characteristics by measuring the lifetime of fluorescent molecular rotor excitation using time-resolved microscopy allows for early monitoring of tumor cells’ sensitivity to photoinduction, and the efficiency of cell death during PDT procedure or immediately after its termination. The functions of molecular rotors were shown for pz I – IV in our previous studies [ 18 , 27 , 28 , 42 , 45 , 46 ]. That means that pz can provide promising prospects for personalized PDT dosimetry aiming to achieve the highest treatment efficacy with minimal cytotoxic effect for surrounding normal tissues.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…The assessment of viscosity characteristics by measuring the lifetime of fluorescent molecular rotor excitation using time-resolved microscopy allows for early monitoring of tumor cells’ sensitivity to photoinduction, and the efficiency of cell death during PDT procedure or immediately after its termination. The functions of molecular rotors were shown for pz I – IV in our previous studies [ 18 , 27 , 28 , 42 , 45 , 46 ]. That means that pz can provide promising prospects for personalized PDT dosimetry aiming to achieve the highest treatment efficacy with minimal cytotoxic effect for surrounding normal tissues.…”
Section: Discussionmentioning
confidence: 86%
“…We have previously shown that pz I – IV effectively kills murine glioma GL261 cells and causes different long-term dark toxicity effects on primary neuronal cultures [ 18 , 19 ]. Herein, we assessed the influence of pz I – IV on the functional network activity of primary hippocampal cultures in a normal state and after PDT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations